Four new anuran defence behaviours observed in the cane toad Rhinella marina. Issue 6 (1st November 2020) - Ferrante, Lucas; Najar, Thainá; Kaefer, Igor L.
Abstract : Defensive behaviours are a prime strategy for animal survivorship. However, the diversity of defence displays still needs systematic studies, since most reports are based on opportunistic field observations. In this study, we explore the defensive behaviour of the cane toad, Rhinella marina, collecting data from 173 individuals. As a result, here we describe four new defensive behaviours for anurans, thus increasing the knowledge about their defence mechanisms, and highlight the need for further systematic and experimental essays.